Association of sedentary behaviour on internalizing problems in children with and without motor coordination problems. (March 2020) - Bulten, Rheanna; Brown, Denver; Rodriguez, Christine; Cairney, John
Abstract: Introduction: Children with motor coordination problems are at increased risk for both sedentary behaviour and internalizing problems relative to their typically developing peers; however, the relationship between motor coordination, internalizing problems, and sedentary behaviour is not well understood. The purpose of this study was to examine the moderating role of sedentary behaviour on the relationship between motor coordination and anxiety/depression scores in children at risk for Developmental Coordination Disorder and a sample of typically developing children. Methods: Data for the present study were derived from the Coordination and Activity Tracking in CHildren (CATCH) cohort study. 507 children aged 4–5 years (219 girls, 288 boys, mean age: 59.3 months) were classified as typically developing (>16th percentile) or at risk for DCD (≤16th percentile) based on Movement Assessment Battery for Children 2nd edition scores. Sedentary and physical activity behaviour were measured using an Actigraph GT3X+ activity monitor device. Parent-reported Child Behaviour Checklist (CBCL) scores were used to assess internalizing problems (i.e. anxiety/depression). Results: Multiple linear regression (moderation) analysis showed sedentary behaviour significantly moderated the relationship between motor coordination and anxiety/depression scores after adjusting for sex, socioeconomic status and physical activity behaviour, Δ R 2 = 0.01, F (1, 500) = 4.31, p = .038. Johnson-Neyman technique revealed children at risk for DCD begin to report significantly higher anxiety/depression scores when their sedentary behaviour is at least 0.27 h per day above the group mean ( M = 7.52 h/day). Conclusion: Above average levels of sedentary behaviour exacerbate internalizing problems among children at risk for DCD. Interventions should focus on incorporating strategies to reduce sedentary behaviour in order to buffer anxiety/depressive symptoms for children with poor motor coordination. Highlights: Sedentary behaviour (SB) measured using accelerometry in 507 TD and rDCD children. No differences in SB or internalizing problems between TD and rDCD groups. Evidence of a moderating effect for SB on internalizing problems in rDCD children. Effect was independent of sex and physical activity behaviour. Slightly above average SB resulted in higher internalizing problems for rDCD children.